Frege as a critic of Kant - Bouveresse, Jacques; Suárez, José Olimpo (Estudios de Filosofía, 1990)
According to Frege, the expression "formal theory of arithmetic" can designate two very different conceptions, he defended one and fought the other. The first is that which attributes to arithmetic a “formal” character, in the sense of “purely logical” that radically distinguishes it from geometry and brings it closer to logic itself. The second is the vulgar formalist conception, according to which in arithmetic “the signs are empty and constitute numbers themselves.”